Doing qualitative research - Silverman, David, 1943- (London Thousand Oaks, California SAGE Publications Ltd, 2017)
'Accessible, practical, and packed with indispensable advice, this bestselling textbook is the perfect hands-on guide for any student embarking on their own research. With expert advice from the author and real-life experiences from students, this book shows you how to go from the ideas of research to the practicalities of designing, conducting, and writing about your research yourself.' -- Provided by publisher.
Note continued: 5.Theorizing as Thinking through Data / Clive Seale -- 6.Writing for Audiences / Clive Seale -- 7.Why Your Concluding Chapter Can Be Fun / Clive Seale -- 8.Wrapping Up / Clive Seale -- Twenty-Six.Surviving an Oral Examination / Clive Seale -- 1.Introduction / Clive Seale -- 2.Viva Horror Stories / Clive Seale -- 3.Preparing for Your Oral / Clive Seale -- 4.Doing the Oral / Clive Seale -- 5.Outcomes / Clive Seale -- 6.Revising Your Thesis after the Oral / Clive Seale -- 7.A Case Study / Clive Seale -- 8.Wrapping Up / Clive Seale -- Twenty-Seven.Getting Published / Clive Seale -- 1.Introduction / Clive Seale -- 2.The Backstage Politics of Publishing / Clive Seale -- 3.Strategic Choices / Clive Seale -- 4.What Journals Are Looking For / Clive Seale -- 5.Reviewers' Comments / Clive Seale -- 6.How to Write a Short Journal Article / Clive Seale -- 7.Wrapping Up / Clive Seale.
First edition published 2000.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology; Qualitative research -- Handbooks, manuals, etc